ANALYSIS OF FACTORS AFFECTING PERFORMANCE OF EMPLOYEES IN OFFICE OF PUBLIC WORK AND SPATIAL PLANNING OF PADANG CITY - Darmasari, Merry; ., Heryanto (Archives of Business Research, 2018)
This study aims to analyze the factors that influence the performance of employees of the public works and spatial planning office of Padang city. Sample selection was done by purposive sampling with a total sample of 98 employees. The data analysis method used in this study is path analysis method, classic assumption test and hypothesis test. Testing in this study was carried out using the SPSS 21 computer program. The variables in this study consisted of additional variables of employee income, work environment, work motivation and employee performance. Testing the first hypothesis shows the results that additional employee income has a positive and significant influence on work motivation, testing the second hypothesis shows the results of the work environment have a positive and significant effect on work motivation, testing the third hypothesis shows that the additional employee income has no significant effect on employee performance, testing the fourth hypothesis shows that the work environment has an influence and is not significant on employee performance, testing the fifth hypothesis shows that work motivation has an influence and is significant on employee performance, the sixth hypothesis testing shows that the additional income of the employee has a significant effect on work motivation and has no impact on employee performance, testing the seventh hypothesis shows that the work environment has a significant and significant influence on work motivation and does not affect employee performance. Finally, the authors suggest the next researcher to further expand the scope of the sample and add variables or other factors that can affect employee performance.